An Empirical Study on the Volatility based on SSE 50ETF - Zhang, Shengnan (2019)
The rapid development of financial derivatives trading has a strong appeal to many investors. When investors are trading, it not only brings them profits but also brings risks. As an essential parameter of risk measurement, volatility has always been one of the core contents of financial research. On February 9, 2015, China’s financial market, the SSE 50ETF option as the first option is officially listed on the Shanghai Stock Exchange, which means that Chinese financial market entered into the age of options. There is no doubt that analyzes the volatility of this option is becoming a hot topic in China. This paper used three different types of data and the suitable calculation methods of volatility to conduct empirical research. As for the historical volatility, this paper using the SSE 50ETF daily return to calculate the return rate. The results of the historical volatility show that the volatility of SSE 50ETF is characterized by volatility clustering, the leptokurtosis and fat-tail, and anti-leverage effect. Secondly, as for the analysis of the realized volatility, choose the five-minute data at the trading day as the research data to establish the HAR-RV model. The results show that the volatility of SSE 50ETF has characteristic of long memory. Finally, for the implied volatility, the SSE 50ETF option data is selected and calculated volatility by using the dichotomy method based on the B-S pricing formula and weighted by options Vega value. The analysis showed that compared with call options, the relation curve between implied volatility and strike price of put options has distinct smile shape when the maturity is fixed. Moreover, when the strike price is fixed, the closer the contract is to maturity, the more intense the implied volatility would be, and the more dispersed the volatility would be. By comparing the empirical results of these three types of volatility, we find that they all have consistency in these features like leptokurtosis and fat-tail, leverage effect, long memory and volatility smile. Besides, the fluctuation trends of these three volatilities are similar and are also in line with financial market developments.